TICs, TPACK e desempenho dos estudantes no ensino superior - Souza, Fernanda Edileuza Riccomini de (2023)
The general objective of this thesis was to analyze the relationships between both ICTs and TPACK with student performance in higher education. For this, interdependent studies were developed. In the first study, entitled “ICTs and student performance in higher education – A Scope Review”, a scope review was conducted - synthesis of knowledge on a topic, with the aim of mapping the area of knowledge with regard to relationships of ICT use with student performance. The main results were: the identification, categorization and analysis of the research fronts with the direction of studies in five themes, in addition to the elaboration of a framework of the observed themes; the analysis of the relationships between the objectives and results of the analyzed studies; the analysis of factors that can impact the relationship between the use of ICTs and student performance; analysis of the conduction of methods applied to research; and the proposal of an agenda for future research. The synthesis of knowledge offered broadened the theoretical scope on the relationship between the use of ICTs and student performance, bringing a new contribution to the literature as it lists the main fronts of research on the subject, presenting topics that go far beyond descriptions of characteristics of publications. In the second study, entitled “TPACK and student performance in higher education”, the objective was to analyze the relationships between TPACK components and student performance and the impacts of the context on these relationships. To achieve the objective, a quantitative empirical research was carried out, which used Bayesian Multilevel Regression as a method for data analysis, which tested the set of hypotheses raised, originating the theoretical model TPACK and student performance with the moderation of two context variables. The research findings indicated that of the nine hypotheses tested, five hypotheses were supported and four were not. Despite the effects of the contexts chosen for the research not having an impact on 35 relationships between the TPACK components and student performance, there are 21 impacted relationships (twelve negative and nine positive), which makes the research developed an opportunity to deepen the theme and new relations tests, in addition to the observation, in particular, of the complete TPACK component, which was negative in relations with student performance in the general context of universities and in public and private administrative categories, and null in the other contextual effects. Still, research related to the use of the TPACK structure to explore the development of knowledge in Higher Education, excluding teacher education, are scarce, however what mainly differentiates this study from other studies on the subject is the analysis of the relationship of two little studied variables together, that is, TPACK and student performance. As a contribution, this thesis brings a broad perspective of how ICTs and teaching knowledge, based on the TPACK model, can relate to student performance. A better understanding of these phenomena can lead to global improvements, such as, for example, the development of public and institutional policies for the training of university professors, as well as evaluations of HEIs, courses, professors and students; encouragement and development of projects and research aimed at improving teaching practice; improvement in teaching, learning outcomes and perceived quality of HEIs; and the preparation of students for the job market and their contribution to society. Such implications can still broaden the gaze of educational managers at HEIs who are concerned with quality education and assertive decision-making to face the challenges of competition in the sector, the digital transformation and also the post-pandemic changes imposed on teaching and learning in higher education. The contributions of this thesis bring new reflections both in the field of administration and education, since the use of ICTs, the TPACK (teacher knowledge), the improvement in student performance, the competitive advantage of HEIs were discussed subjects.